Synergic strengthening by oxide and coherent precipitate dispersions in high-entropy alloy prepared by powder metallurgy. (December 2018) - Moravcik, Igor; Gouvea, Larissa; Hornik, Vit; Kovacova, Zuzana; Kitzmantel, Michael; Neubauer, Erich; Dlouhy, Ivo
Abstract: The present work deals with the synthesis and evaluation of the microstructural and mechanical properties of face-centred cubic Ni1.5 Co1.5 CrFeTi0.5 high-entropy alloy strengthened by nano-sized titanium oxide dispersion and coherent precipitates of Ni3 Ti intermetallic phase produced by powder metallurgy. The alloy's properties are well tuneable by the use of proper heat treatment. The alloy exhibits an excellent combination of tensile strength and ductility, reaching an ultimate tensile strength of 1460 MPa and elongation of 14.5% in solution annealed state and 1660 MPa and 4.8% in the aged condition. Most of the strengthening contribution was attributed to Orowan-type strengthening mechanism. Graphical abstract: Unlabelled Image